Analisis Pengeluaran Pemerintah Bidang Kesehatan dan Pendidikan Terhadap Indeks Pembangunan Manusia Di Provinsi Sulawesi Utara - Kolinug, Ferly Christian; Rompas, Jeifer Juandy Livingstone; Betrix, Betrix (Politeknik Raflesia Press, 2024)
The purpose of this study is to analyze the influence of government expenditure in the health and education sector on the Human Development Index in North Sulawesi province in the last eleven years. This study uses secondary data taken from the Central Statistics Agency of North Sulawesi and the Directorate General of Financial Balance for the period 2012 – 2022. The analysis used was a multiple regression analysis of panel data that combined data from 15 city districts using a panel data analysis model on the eViews application with data collection on government expenditure in the health sector, education sector and human growth index. Regression testing showed Y = 648 + 2.68 X1 + 1.04 X2. The T test explained that the Education variable has a significant influence on HDI and the results of the Health variable have a significant influence on HDI, the amount of government expenditure on education and health can be seen from the Adjusted R-square of 0.73 which means it has an effect of 73 percent and the rest by other factors.